Aggressive angiomyxoma in pregnancy: a case report and literature review. Issue 7 (July 2020) - Xu, Haihua; Sun, Pengming; Xu, Rongli; Wang, Lihua; Shi, Yuequan
Aggressive angiomyxoma is an interstitial tumour that is often misdiagnosed and is likely to recur. There have been few reported cases of angiomyxoma in pregnant women. We report a case of a woman who was previously diagnosed with a tumour in her vulva that increased in size during both of her pregnancies and spontaneously decreased postpartum. Local excision was performed and a gonadotropin-releasing hormone agonist was administered. According to a literature review, aggressive angiomyxoma is associated with good maternal and child outcomes. Caesarean section is not the delivery method of choice, but it is indicated if the tumour is preventing vaginal birth. Treatment for angiomyxoma is mainly postpartum local resection supplemented by hormone therapy. This tumour frequently recurs and patients should undergo long-term follow-up.